PERENCANAAN TENAGA KERJA DAN BIAYA TENAGA KERJA PADA PEKERJAAN BETON STRUKTUR KOLOM - Dian Febrianti; Zakia zakia (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2019)
The project is a group of interconnected activities where there are starting points and end points and certain results. Projects usually require various skills from various professions and  organization.  The  resources  used  during  construction  are  men,  money,  materials, machines, methods, marketing, and information. Manpower / human resources is one of the most important factors of project success. In addition, another important factor is planning labor costs, because to find out the amount of costs incurred on the project. The purpose of this study is to find out the labor requirements and the amount of labor costs, as well as knowing the accumulation of labor needs and the greatest costs for a given week and the causes, especially the concrete work of column structures. In writing this final project, the method of calculating the amount of labor and costs is used with the help of Microsoft Excel, then visualized through graphics. The data used in this study is secondary data consisting of drawing plans, Budget Plan (RAB), time schedule, progress, and work plans. This study resulted in the calculation of labor requirements, in the column structure, namely 582.21 OH. With details, workers 442.96 OH, artisan94.29 OH, artisan head 23.46 OH, and Overseer 21.51 OH. The labor cost needed to finance this work is Rp. 26,249,643.00. The use of the largest costs occurs at week 4, costs Rp. 4,902,580.00 and the smallest costs occur at week 2 of Rp. 337,608.00. Based on this research, labor requirements and labor costs have been well distributed